2023
DOI: 10.3390/ijgi12070270
|View full text |Cite
|
Sign up to set email alerts
|

Construction Method for a Three-Dimensional Tunnel General Monomer Model Based on Parallel Pathfinding

Abstract: Existing approaches for the 3D modeling of tunnels suffer from several problems, such as highly difficult data acquisition, redundancy of model data, large computational burden, and the inability of the resulting models to be monolithic. Therefore, solutions to the tunnel network modeling problem for complex structures need to be proposed and elaborated in detail. In this paper, a construction method for a three-dimensional tunnel general monomer model based on parallel pathfinding is proposed. Widely used tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In detail, pathfinding can be divided into three steps: (1) identify and define the starting and ending points of the rescuer in the entire road network model. (2) Calculate each part of the path. (3) Obtain a continuous path.…”
Section: Emergency Pathfindingmentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, pathfinding can be divided into three steps: (1) identify and define the starting and ending points of the rescuer in the entire road network model. (2) Calculate each part of the path. (3) Obtain a continuous path.…”
Section: Emergency Pathfindingmentioning
confidence: 99%
“…Urban transportation therefore becomes more intricate due to the emergence of so many buildings, and so will indoor transportation as such buildings always have a large number of semienclosed spaces and obstacles. It has been reported that people spend about 90% of their days indoors, engaged in activities such as entertainment, education, work, dining, and so on [1][2][3]. Once an emergency such as a fire or explosion occurs inside a building, the cost of rescue will be considerably increased.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the development of geographical digital twin technologies, intelligent construction has gradually become an essential direction for tunnel excavation [6,7]. By constructing a digital twin geographical scene of tunnel excavation and establishing a dynamic connection between the physical world and the information world, it is possible to accurately control changes in tunnel excavation, which can alleviate or even eliminate the problem of over-and under-excavation during the construction process [8,9]; however, current geographical twin models in tunnel engineering primarily focus on modeling and visual description, and there are few studies in which digital twin ideas are integrated into deformation diagnosis during construction [10][11][12]. The lack of diagnostic analysis functions has become a significant obstacle to achieving intelligent construction and precise management of tunnel projects.…”
Section: Introductionmentioning
confidence: 99%